Pengenalan Digital Marketing Untuk Meningkatkan Kapasitas UMKM Di Dukuh Pedak - Sabania, Kania Irfa; Setiawan, Doni Agus; Ghanny, Rama; Khadapi, Muhammad Muamar; Wicaksono, Ahda Sabila; Saputra, Wijaya Whilly Hanggo; Pranoto, Bambang; Tariska, Rara Reza; Maharani, Widya Putri; Aprilia, Cahya; Muallidin, Isnaini (Universitas Muhammadiyah Yogyakarta, 2025)
This article presents the results of the Community Service Program with the theme